2021
DOI: 10.24912/jmieb.v5i1.10023
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants Factors of Profitability Islamic Bank in Indonesia

Abstract: Tujuan dari penelitian ini adalah untuk mengetahui faktor yang mempengaruhi pertumbuhan dari profitabilitas bank syariah di Indonesia. Penelitian ini menggunakan pendekatan kuantitatif dengan metode Autoregressive Distributed Lag (ARDL). Data yang digunakan adalah data bulanan variabel makroekonomi dan variabel perbankan periode Januari 2006 – Desember 2019. Variabel makroekonomi yang digunakan adalah Industrial Production Index, Inflasi, Nilai Tukar Rupiah terhdap dollar, suku bunga. Sedangkan variabel perban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 7 publications
2
15
0
3
Order By: Relevance
“…The high FDR shows the greater the financing, and the higher the financing will be able to increase profits, because Islamic banks gain the most from financing. The results of research from (Sudarsono et al, 2021;Purwasih & Wibowo, 2021;and Widarjono, 2018) who conducted research on Islamic banks found a positive effect between FDR and profitability. Conventional banks also found a positive effect between liquidity risk and profitability (Koroleva, Jigeer, Miao, & Skhvediani, 2021;and Sofyan, 2019).…”
Section: Liquidity Risk and Profitabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The high FDR shows the greater the financing, and the higher the financing will be able to increase profits, because Islamic banks gain the most from financing. The results of research from (Sudarsono et al, 2021;Purwasih & Wibowo, 2021;and Widarjono, 2018) who conducted research on Islamic banks found a positive effect between FDR and profitability. Conventional banks also found a positive effect between liquidity risk and profitability (Koroleva, Jigeer, Miao, & Skhvediani, 2021;and Sofyan, 2019).…”
Section: Liquidity Risk and Profitabilitymentioning
confidence: 99%
“…Widyakto & Wahyudi (2021) and Kryeziu & Hoxha (2021) found a positive effect of CAR on profitability. On the other hand, Purwasih & Wibowo (2021) and Durguti, Krasniqi, & Krasniqi, (2020) found that CAR had a negative effect on profitability, while Sudarsono, Afriadi, & Suciningtias (2021) actually found CAR and profitability has no effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salah satu indikator penting dalam suatu perekonomian adalah stabilitas bank karena bank merupakan jantung perekonomian (Purwasih & Wibowo, 2021). Bank syariah memiliki peran sebagai lembaga perantara (intermediary) antara unit-unit ekonomi yang mengalami kelebihan dana (surplus units) dengan unitunit lain yang mengalami kekurangan dana (deficit units).…”
Section: Pendahuluanunclassified
“…2022, Jurnal Tabarru' : Islamic Banking and Finance 5 (2) : 499 -512 Perbankan syariah sebagai bagian dari sistem keuangan Indonesia dinilai lebih tangguh dalam menghadapi krisis dibandingkan bank konvensional (Purwasih & Wibowo, 2021) (Otoritas Jasa Keuangan, 2021). Bank syariah di Indonesia sendiri terus menunjukkan perkembangan yang positif dari tahun ke tahun.…”
Section: Pendahuluanunclassified